Solar wind controls on Mercury's magnetospheric cusp. Issue 6 (14th June 2017) - He, Maosheng; Vogt, Joachim; Heyner, Daniel; Zhong, Jun
Abstract: This study assesses the response of the cusp to solar wind changes comprehensively, using 2848 orbits of MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) observation. The assessment entails four steps: (1) propose and validate an approach to estimate the solar wind magnetic field (interplanetary magnetic field (IMF)) for MESSENGER's cusp transit; (2) define an index σ measuring the intensity of the magnetic disturbance which significantly peaks within the cusp and serves as an indicator of the cusp activity level; (3) construct an empirical model of σ as a function of IMF and Mercury's heliocentric distance r sun, through linear regression; and (4) use the model to estimate and compare the polar distribution of the disturbance σ under different conditions for a systematic comparison. The comparison illustrates that the disturbance peak over the cusp is strongest and widest extending in local time for negative IMF B x and negative IMF B z, and when Mercury is around the perihelion. Azimuthal shifts are associated with both IMF B y and r sun : the cusp moves toward dawn when IMF B y or r sun decrease. These dependences are explained in terms of the IMF B x ‐controlled dayside magnetospheric topology, the component reconnection model applied to IMF B y and B z, and the variability of solar wind ram pressure associated with heliocentric distance r sun . The applicability of the component reconnection model on IMF B y indicates that at Mercury reconnection occurs at lower shear angles than at Earth. Plain Language Summary: Mercury's magnetosphere was suggested to be particularly sensitive to solar wind conditions. This study investigates the response of the magnetospheric cusp to solar wind conditions systematically. For this purpose, we analyze the statistical predictability of interplanetary magnetic field (IMF) at Mercury, develop an approach for estimating the solar wind magnetic field (IMF) for MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER's) cusp transit, construct an indicator for the activity level of the cusp, build an empirical model for the indicator as a function of solar wind variables from 3 years of the MESSENGER measurements, and compare the cusp activity under different conditions. Results demonstrate that the azimuthal location, horizontal extension, and the internal magnetic disturbance are dependent on all IMF components as well as on Mercury's heliocentric distance. These results provide evidence and clues to fundamental processes of solar wind and magnetosphere interactions. Key Points: IMF predictability and IMF estimation at Mercury, magnetic disturbances as indicators of the cusp, and a new empirical modeling of the cusp The horizontal location and extension of the cusp are susceptible to all IMF components and Mercury's heliocentric distance The IMF B y dependence is opposite to that at Earth, revealing that reconnections occur at lower shear angles at Mercury than at Earth